Development of transport by telematics : 19th International Conference on Transport System Telematics, TST 2019, Jaworze, Poland, February 27 - March 2, 2019 : selected papers /: 19th International Conference on Transport System Telematics, TST 2019, Jaworze, Poland, February 27 - March 2, 2019 : selected papers. ([2019]) - Unknown
No abstract available